PERAN PENYULUH PERTANIAN TERHADAP KINERJA USAHATANI JAGUNG DI DESA ALEBO KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Nurhayani Liadi; La Nalefo; Yoenita Jayadisastra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to investigate the activities of agriculture teachers in Alebo Village, Konda District, South Konawe Regency. The objective is to evaluate the effectiveness of corn cultivation in Alebo Village, Konda District, South Konawe Regency. The research was carried out in Alebo Village, Konda District, Regency. Konawe Selatan is predominantly an area for the cultivation of corn and vegetables. The study was carried out between April and May 2023, utilising a sample of 20 farms. The analysis employed the class interval formula and Spearman rank correlation, utilising SPSS 25. This research utilises a quantitative approach, employing descriptive analysis and Spearman rank correlation for data examination. This research indicates that agricultural instructors in Alebo Village serve effectively as facilitators, motivators, innovators, and educators. The correlation coefficient generated in this study is significant. A significant association exists between the role of agricultural teachers and the success of farming companies in Alebo Village, Konda District, South Konawe Regency.